Compreensão leitora e consciência textual, considerando atenção e hábitos de leitura : um estudo com alunos de Ensino Fundamental/9º ano e Ensino Médio/3º ano - Rosa, Gabrielle Perotto de Souza da (2019)
The aim of this thesis was to evaluate the relationship between reading comprehension and textual awareness performance, considering attention and reading habits. The specific objectives were to verify the reading comprehension performance and the textual awareness of students of 9th grade and 3rd year of high school; verify the characteristics of reading habits of these students; verify the performance of these students in Concentrated Attention and Alternating Attention; to analyze the correlations between reading comprehension, textual awareness, attention and reading habits, evidenced by the students according to the collected data. The sample consisted of 47 students from two the last year of the elementary school and 47 students from two last year of the high school classes, totaling 90 students from two state public schools in Porto Alegre / RS. The data was collected by instruments suitable for these variables - reading comprehension, textual awareness, attention and reading habits - and then collected, organized, statistically treated (by the Pearson (r) linear correlation coefficient calculation), analyzed. and discussed. It was noticed in this research, that in the Reading Comprehension / Cloze instrument in both levels of education the subjects obtained an average score higher than that considered acceptable for Taylor (1953), as well as in the Reading / Recount Understanding instrument and in the Textual Awareness instrument. In the Reading Comprehension / Anomalies instrument both groups obtained low averages, considering the total anomalies that should be found. The subjects' averages in the Concentrated Attention test at both levels of education were below the test average. In the Alternate Attention Test mean subjects were above the average of the test in elementary school and below in high school. As for reading habits, in elementary school the reading subjects were represented by 85.6% and in high school the total reading students was 67.4%. In both groups most students considered reading an interesting activity. The correlations between the analyzed variables were verified by Pearson's linear correlation coefficient (r). Pearson coefficient values were interpreted according to Dancey and Reidy (2006). Some results showed a moderate correlation, such as between the results of the subjects in the Reading Comprehension / Cloze and Reconto instruments (r = 0.51), and between the results of the subjects in the Textual Awareness and Reading Comprehension / Cloze instruments (r = 0, 65) in high school; and showed a strong correlation between the subjects' results in the Textual Awareness and Reading Comprehension / Cloze instruments (r = 0.73) in the ninth grade. In the 9th grade group the correlation between the results of the instruments obtained through the Textual Awareness and Reading Comprehension / Cloze instruments was strong, as was the correlation between the results obtained through the questions of the Reading Habits instrument linked to Reconto. The correlations between the results obtained through the Reading Habits instrument questions linked to the Textual Awareness and the correlations between the results obtained through the Reading Habits instrument questions linked to the Reading Comprehension / Anomalies were considered moderate. The correlations between the results obtained through the Attention Tests and between the results obtained through the questions of the Reading Habits instrument and the Reading / Cloze Comprehension instrument were considered weak. The correlations between the other results obtained through the instruments of this research were considered weak and negligible. In the 3rd year high school group the correlation between the results of the instruments obtained through the Textual Awareness and Reading Comprehension / Cloze instrument was moderate, as was the correlation between the results obtained through the questions of the Reading Habits instrument linked to Textual Awareness. We also considered moderate correlations between the results obtained through the Reading Comprehension / Clone and Cloze comprehension instruments and between the results obtained through the Reading Habits / Anomalies Reading Instrument related questions. The correlations between the results obtained through the Reading Habits instrument and the Reading Comprehension / Retelling instrument were considered weak. The correlations between the other results of the instruments of this research were considered weak and negligible. The analysis of reading comprehension, textual awareness, reading habits and attention reveals that some subjects are aware of the lack of attention during reading, as answered in the Reading Habits instrument. However, as there was no significant correlation between the results of these variables, it is not worth stating that the lack of attention in specific tests to measure it presupposes the subjects' performance in Reading Comprehension and Textual Awareness instruments. Based on the data collected and the analyzes performed some work suggestions and methodological contributions were proposed to help the reading comprehension of the students. Considerations were proposed about research that includes attention and reading and suggestions for future studies.